Development of a Clean-Label Meat-Free Alternative to Deli Ham - Lisiane Carvalho; Beatriz Caetano; Capucine Godinot; Norton Komora; Adriana Ferreira; Célia Rocha; Bruna Barbosa; Anabela Raymundo; Isabel Sousa (Foods)
Reducing meat consumption is a key strategy to mitigate environmental impact, lower the incidence of diet-related diseases, and promote sustainable food production. In response, the plant-based food market has grown significantly, motivated by demand for meat-like products. This study aimed to develop a meatless alternative to deli ham (MAD) free of chemical additives, adhering to clean label principles. A commercially available MAD product (Target MAD) was used as a benchmark. Based on its analysis, clean-label laboratory (Optimized CL formulation) and pilot-scale (CL MAD) prototypes were developed. These were evaluated for texture, rheology, color, sensory attributes, and physicochemical properties. The CL MAD demonstrated similar firmness to the Target MAD, while being 17% more cohesive and 50% less adhesive. Its mechanical spectra showed typical weak gel behavior, with G′ higher than G″. Color analysis indicated that the CL MAD was darker and less pink than the Target MAD. Nutritionally, it provided higher protein and lower fat content. Overall, this study successfully developed a clean-label meat-free alternative to deli ham that matches commercial textural standards while offering improved nutritional quality and eliminating chemical additives, meeting growing consumer demand for healthier and more sustainable foods.